Xenophobia:: Scope and Motivations - Salih, Ahmed M. (Al-Adab Journal, 2019)
To treat foreigners nicely or nastily is attributed to traditions and norms of host society because some societies are friendly, others are not. The bad attitudes towards outsiders are expressed in forms of either physical or verbal behaviour. Various motivations encourage native citizens to create images to label non-natives or outsiders. Continuous contact and education can bridge the gap between the two groups. Also, they develop positive and mutual understand that might help them to work for the good of all and live peacefully. It is the responsibility of governments and individuals of society to work hard to dispel fears of foreigners especially in places where violence is expected to happen. This paper tries to lay an outline (model) for the phenomenon of xenophobia in language so that definition, classification, motivations, and lists of xenophobic expressions are presented. It is hypothesized that certain factors are behind generating hostility and xenophobic expressions in society. Additionally, attitudes can be changed to create an appropriate and suitable environment for society members.